Pengendalian Kualitas Proses Pengemasan Gula Dengan Pendekatan Six Sigma - Kusumawati, Aulia; Fitriyeni, Lailatul (Jurnal Sistem dan Manajemen Industri, 2017)
The main factor to achieve business success in the era of globalization is quality. Quality control is key in maintaining customer loyalty. In the company's production process is still found the resulting product does not comply with the specified specifications. This study aims to determine the value of sigma and factors causing damage to the production process of bagging section For companies with quality control is expected to achieve corporate goals. In this study, the methods used is Six Sigma with define, measure, analyze, improve. Six Sigma result is measurement of company performance baseline at measurement stage that is company at condition 5,1 sigma with DPMO equal to 162,4532. The factors causing the disability of sugar packing are lack of research and skill of the operator, instability of conveyor speeds and jet engine position, machine hygiene condition, lack of weighing machine, and ineffective treatment, and control method.